Fourteen new species of the spider genus Psiloderces Simon, 1892 from Southeast Asia (Araneae, Psilodercidae) - Wan-Jin Chang; Shuqiang Li (ZooKeys, 2020)
The genus Psiloderces Simon, 1892 is the second largest genus of Psilodercidae, a family restricted to Asia, occurring from East India to the Philippines. Fourteen new species of Psiloderces from Indonesia, the Philippines, and Vietnam are described: P. heise sp. nov. (♂♀), P. gawanaensis sp. nov. (♂♀), P. bontocensis sp. nov. (♀), P. cuyapoensis sp. nov. (♂♀), P. xichang sp. nov. (♂♀), P. cattienensis sp. nov. (♂♀), P. pingguo sp. nov. (♂♀), P. palopoensis sp. nov. (♂♀), P. penajamensis sp. nov. (♂), P. grohotensis sp. nov. (♂♀), P. bangkiraiensis sp. nov. (♂♀), P. bolang sp. nov. (♂♀), P. wangou sp. nov. (♂♀), and P. malinoensis sp. nov. (♂♀). Types are deposited in the Institute of Zoology, Chinese Academy of Sciences (IZCAS) in Beijing.